Soil Organic Carbon Losses: The Balance between Respiration and Leaching, and Phosphorus Mobility in Lateritic Soils - Yusran, Fadly Hairannoor (JOURNAL OF TROPICAL SOILS, 2010)
Soil Organic Carbon Losses: The Balance between Respiration and Leaching, and Phosphorus Mobility in Lateritic Soils (FH Noor): Organic matter (OM) application may contribute to managing lateritic soils by improving aspects of physical, chemical, and biological fertility.  However, the finite persistence of organic carbon (OC), the main component of soil organic matter (SOM), may limit the usefulness of OM addition because decomposition and C leaching promotes C loss from the soil, especially in tropical regions.  The main objectives of this study were to determine the balance and dynamics of soil OC (SOC) due to mineralisation and leaching processes and the relationship of these processes to P mobility in soil.  Two lateritic soils of Western Australia were used.  Both soils were packed into plastic columns and water was added to simulate two rainfall regimes: tropical (4,000 mm year 1) and subtropical (900 mm year 1).  Three types of OM (peat, wheat straw, and lucerne hay) were added at the equivalent of 80Mg ha 1.  Soils were watered weekly to supply one year’s rainfall over a period of six months.  Carbon loss from leaching contributed 1.4% of the total C, whilst respiration accounted for 10.4%.  The Ultisol with a sandy texture had more C loss in leachate than the Oxisol with higher clay content, for the simulated tropical rainfall.  The subtropical rainfall regime resulted in more respiration than the tropical rainfall regime.  Downward movement of dissolved organic carbon (DOC) changed the distribution of non-extractable phosphorus (NP) and bicarbonate phosphorus (BP) in the leaching column, as well as the dislocation of extractable Al and Fe.